2007
DOI: 10.1124/jpet.106.114934
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Induces Apoptosis in Human Vascular Smooth Muscle Cells from Diabetic Patients Involving the Transforming Growth Factor-β/Activin Receptor-Like Kinase-4/5/7/Smad2 Signaling Pathway

Abstract: Alterations in vascular wall remodeling are a typical complication in type 2 diabetes mellitus due to an imbalance between cell proliferation and apoptosis. In this context, we have previously shown that vascular smooth muscle cells (VSMC) from diabetic patients were resistant to induced apoptosis. Thiazolidinediones, such as pioglitazone, seem to exert direct antiatherosclerotic effects on type 2 diabetes. Here, we aimed to study whether pioglitazone was able to induce apoptosis in VSMC from diabetic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…These concentrations were based on previous studies that used cell cultures systems [17,33] and showed protective effect of vitamin B12 on DNA damage of drugs other than pioglitazone [17]. Based on results of the current study, investigation of a range of concentrations of the combination pioglitazone and vitamin B12 is recommended for future studies.…”
Section: Discussionmentioning
confidence: 92%
“…These concentrations were based on previous studies that used cell cultures systems [17,33] and showed protective effect of vitamin B12 on DNA damage of drugs other than pioglitazone [17]. Based on results of the current study, investigation of a range of concentrations of the combination pioglitazone and vitamin B12 is recommended for future studies.…”
Section: Discussionmentioning
confidence: 92%
“…TGF-β1 exerts its neovascularization effects at several levels: control of vascular cell proliferation, maintenance of differentiation, and increased immunomodulatory and anti-inflammatory actions. Some traditional drugs such as aspirin (Redondo et al, 2003;Nakamura et al, 2006) and pioglitazone (Redondo et al, 2005;Ruiz et al, 2007) act on the TGF-β1 pathway. TGF-β1 is also known to enhance tendon repair during the fibrosis period in vitro and vivo by increasing cell proliferation, migration, and the synthesis of both collagen and proteoglycan.…”
Section: Introductionmentioning
confidence: 99%
“…In VSMC, its canonical pathway involves signalling by ALK-5 receptor, which phosphorylates the Smad family proteins and translocate into the nucleus to regulate gene expression [8]. The ALK-5/phospho-Smad2 (PSmad2)-dependent signalling pathway has been linked to apoptosis in human VSMC [9]. Nevertheless, in cultured VSMC the importance of TGF-β1-dependent p38 MAPK signalling when TGF-β1 induces proliferation arrest in the absence of apoptosis has equally been described [10].…”
Section: Introductionmentioning
confidence: 99%